Knowledge Management, Financial Reporting Compliance, and Village Financial Management Performance: Competence as a Mediating Variable - Nurharibnu Wibisono; Siti Suharni; Mintarti Indartini (AKRUAL: JURNAL AKUNTANSI, 2026)
Introduction/Main Objectives: This study aims to examine the effects of knowledge management and financial reporting compliance, both directly and indirectly, on the performance of village financial management as it is mediated by competency. Background Problems: After the enactment of Law 6 of 2014 abaout Villages, the village government had difficulties in enhancing the effectiveness of financial management inside the village and a high incidence of financial corruption. Novelty: It is hoped that this research can contribute to the importance of competencies that can bridge the influence of knowledge management and compliance with financial reporting on village financial management performance. Research Methods: This research employs a quantitative methodology. The research sample was all villages (10 villages) in Wonoasri sub-district, Madiun district, Indonesia. The data processing technique uses path analysis. Finding/Results: According to this study, knowledge management (KM) having no discernible impact on the village financial management performance (VFMP), financial reporting compliance (FRC) has a significant impact on village financial management performance (VFMP), and competency (Cp) has no significant effect on VFMP. KM and FRC have a significant partial effect on Cp. Cp does not mediate the influence of KM on VFMP. Cp does not mediate the effect of  FRC on VFMP. Conclusion: Village governments need to build KM to improve VFMP performance. Increasing the Cp of village government officials is needed to mediate the influence of KM and FRC on improving Village Government performance.